KUALITAS PELAYANAN DIVISI TOUR DI PT.URBANITAS NUSANTARA BERKAARYA PEKANBARU - Latifah "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Service quality is one of the indicators for consumers to assess companies engaged in services. This study aims to determine the service of the tour division and find out the consumer's response to the quality of service at PT. Urbanitas Nusantara Berkarya Pekanbaru. This research uses descriptive method with a quantitative approach. The sample of this study was 100 respondents. While the data collection techniques in this study use questionnaires, observation, interviews and documentation. By using a Likert scale as a measuring tool to determine the length of the short interval. Based on the research conducted, respondents who said they were satisfied with the services provided based on five sub-variables, namely Tangible as many as 64 respondents, Reliability 84 respondents, Responsiveness 60 respondents, Assurance 65 respondents, and Empathy 62 respondents.Keywords: Quality, Service, Tour Division, Travel Agent